Cannibalization and option value effects of secondary markets: Evidence from the US concert industry - Bennett, Victor M.; Seamans, Robert; Zhu, Feng (Strategic Management Journal, 2015)
We examine how reducing search frictions in secondary markets affects the value appropriated by firms in primary markets. We characterize two effects on primary‐market firms caused by intermediaries entering secondary markets: the “cannibalization” and “option value” effects. Separation between primary and secondary markets can drive which of the two effects dominates. Firms selling valuable and scarce products are more likely to have separate primary and secondary markets, and will therefore appropriate more value when secondary markets thicken. Firms selling products that are not valuable and scarce will be hurt. Further, we hypothesize that firms have incentives to engineer scarcity by limiting supply when secondary markets thicken to separate primary and secondary markets. We find support for these hypotheses in the U.S. concert ticket industry . Copyright © 2014 John Wiley & Sons, Ltd.